The Effect Of Artemether on Mechanical Contractility: Reproductive Smooth Muscle Pharmacology - Tologbonse, Adedoyin; O. Olorunsola, Emmanuel; E. Otimanam, Hillary; N. Onwuka, Amanda; E. Essien , Grace; J. Akpan, Emem; O. C Mbagwu, Herbert (Nigerian Journal of Pharmaceutical and Applied Science Research, 2021)
This study investigated the effect of artemether on smooth muscle contractility to drug regnant female mice. The effect of artemether on isolated uterine smooth muscle strips mounted on organ bath were studied using twenty-five (25) matured pregnant female albino mice (25 -30g). The study further investigated the effect of artemether on sub-acute histopathological examination of the uterus using standard in vivo procedures/ protocols in mice infected with Plasmodium bergheiberghei; the mice in the test group were divided into three(3) subgroup (n=5) and were treated with 1.5 mg/ml ,3.0 mg/ml and 6.0 mg/ml of artemether respectively for five days. Data obtained from the study were represented on table, graph and photomicrographs. The results of this study revealed that artemether (4x10-4 to 4x10-1 mg/ml) alone did not produce contractile responses, but caused significant inhibition on contractile responses induced by oxytocin (4x10-7 to 4x10-4 I.U/ ml.) and acetylcholine (1x10-4 to 1x10- 1 mg/ml) on isolated uterine smooth muscle tissue in mice in a dose dependent manner (p<0.05); also, the Emax of Oxytocin ( 4x10-4 I.U/ ml) is Emax of 22.5 ±. 2.0 mm while acetylcholine (1x10-1 mg/ml) Emax = 4.5 ±. 1.0 mm Artemether significantly reduced the Emax of oxytocin( 4x10-4 I.U/ ml) and acetylcholine (1x10-1 mg/ml) respectively on uterine smooth muscle strips to 11.0 ±. 1.0 mm and 2.9 ± 1.0 mm respectively, (p<0.05- 0.01); histopathological examination also revealed normal uterine smooth muscle profile with slight epithelia lining and cellular degradation .It was concluded that artemether possessed great and safe pharmacological properties.